Analisis Komentar Netizen terhadap Kritik Dai TikTok Kepada Dai Televisi - Danasty Naesyah Wandina; Abdul Basit (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This research was conducted to analyze netizens' comments on the criticism made by Ustadz Rizqi Asfianudin (a TikTok preacher) towards Ning Umi Laila, who discussed the proper way to perform ablution on the RCTI television station's program "Bunga-Bunga Hati Edisi Ramadhan" for the year 2024 or 1445 Hijriyyah. Ustadz Rizqi's criticism sparked both pro and con comments among netizens. The researcher conducted observations of netizens' comments on the critical content and collected documentation to obtain research data. The data obtained will be analyzed using qualitative research methods with a virtual ethnography approach. The analysis in this research goes through the stages of the object level. (media objek). The research results show differences in responses or reactions indicated by netizens in the comment section, namely; 1) Supporting Ustadz Rizqi, 2) Supporting Ning Umi Laila, 3) Not supporting either or neutral, and 4) Mentioning another preacher.